2013
DOI: 10.1590/s1984-29612013005000015
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of four ornamental fish from the Chumucuí River (Bragança, Pará, Brazil)

Abstract: The objective of the present study was to evaluate the parasite fauna of four species of ornamental fish collected in the Chumucuí River, municipality of Bragança, Pará, Brazil. From June 2006 to December 2007 belonging to four species were collected, including 23 specimens of Moenkhausia sanctaefilomenae (redeye tetra), 37 Carnegiella strigata (marbled hatchetfish), 7 Chilodus punctatus (spotted headstander), and 240 Astyanax bimaculatus (twospot astyanax). The parasites found belonged to three taxa: monogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…The most common ornamental fish parasites are Monogenea (platyhelminths), as reported by Fujimoto et al (2013) in Moenkhausia sanctaefilomenae and Astyanax bimaculatus. Other important parasites are protozoa of the phylum Ciliophora, for example Ichthyophthirius multifiliis and Trichodina sp, previously reported by Thilakaratne et al (2003) in Pterophyllum scalare and Kim et al (2002) in Puntius tetrazona.…”
Section: Introductionmentioning
confidence: 82%
“…The most common ornamental fish parasites are Monogenea (platyhelminths), as reported by Fujimoto et al (2013) in Moenkhausia sanctaefilomenae and Astyanax bimaculatus. Other important parasites are protozoa of the phylum Ciliophora, for example Ichthyophthirius multifiliis and Trichodina sp, previously reported by Thilakaratne et al (2003) in Pterophyllum scalare and Kim et al (2002) in Puntius tetrazona.…”
Section: Introductionmentioning
confidence: 82%
“…Until now, nine species of Quadrigyrus are considered valid (Amin 2013). From these, four species (Quadrigyrus brasiliensis Machado Filho, 1941, Quadrigyrus machadoi Fabio, 1983, Quadrigyrus nickoli Schmidt & Hugghins, 1973 were reported from South America (Thatcher 2006, Santos et al 2008, Fujimoto et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, there are reports of Q. torquatus from different hosts collected in States of Pará, Mato Grosso, Rio de Janeiro and Paraná (Machado Filho 1941, Carvalho et al 2003, Guidelli et al 2006, Santos et al 2008, Fujimoto et al 2013, but no records have been made for Rio Grande do Sul State. The present study reports for the first time the acanthocephalan Q. torquatus in two species of Astyanax from Lake Guaíba, southern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of parasites in ornamental fishes has been reported worldwide as well as Indonesia. Parasites in ornamental fishes that determined from Chumuci River in Mexico were from 3 taxas , namely Monogenean, Nematoda and Acantocephala [6]. In Korea, 7 imported fishes from Southeast Asia were examined for parasite infection and they found that there were 3 ciliates, 2 monogeneans, 1 nematode, and 1 copepod from 7 host species [7].Aquarium fishes that colected from pet shop in Sweden mostly infected by Monogenea parasites [8].…”
Section: Introductionmentioning
confidence: 99%